Revisiting Cross-Country Poverty Convergence in the Developing World with a Special Focus on Sub-Saharan Africa - Yusi Ouyang; Abebe Shimeles; Erik Thorbecke (Institute of Labor Economics (IZA), 2018)
The literature on poverty convergence is sparse and much of the empirical evidence relies on Ravallion (2012) who found a lack of poverty convergence across some ninety Less Developed Countries (LDCs) during 1977-2007. This paper revisits cross-country poverty convergence using data from the same sources but an extended period, i.e. 1977-2014. We find that while poverty convergence remains absent across LDCs during 1981-2014, it is explained by initial poverty nullifying the effectiveness of growth in reducing poverty; whereas an adverse direct effect of initial poverty on growth – which is recognized as the main impediment to cross-country poverty convergence during 1977-2007 – is not found. In SSA, in contrast, we find strong cross-country poverty convergence during both periods examined, as an adverse direct poverty effect is not found, and the indirect poverty effect is not large enough to cancel the mean convergence effect.
Keywords: O10; O55; 330; cross-country poverty convergence; growth; poverty; Sub-Saharan Africa